Concise encyclopedia of modelling & simulation - Atherton, Derek P.; Borne, Pierre (Advances in systems, control, and information engineering., 1992)
The Concise Encyclopedia of Modelling & Simulation contains 172 alphabetically arranged articles describing the modelling and simulation of physical systems. The emphasis is on mathematical models and their various forms, although other types of models, such as knowledge-based, linguistics-based, graphical and data-based, are also discussed. The articles are revised from the Systems & Control Encyclopedia, and many newly commissioned articles are included describing recent developments in the field. Articles on identification cover all aspects of this problem, from the use and choice of specific test signals to problems of model order and the many algorithms and approaches to parameter estimation. Computational techniques, such as the finite-element method, that play an important role in analyzing nonlinear models are covered. Articles outline the development of simulation, consider currently available simulation languages, describe applications and cover current developments in the area. Where appropriate, illustrations and tables are included to clarify particular topics. This encyclopedia will be a valuable reference source for all practising engineers, researchers and postgraduate students in the field of modelling and simulation.